1977
DOI: 10.1104/pp.60.1.170
|View full text |Cite
|
Sign up to set email alerts
|

Proof for the Production of Cutinase by Fusarium solani f. pisi during Penetration into Its Host, Pisum sativum

Abstract: Rabbit antibody to cutinase-I, isolated from Fusarium solani f. pisi, was conjugated to ferritin. With this fermtin-conjugated antibody it was shown that germinating spores of this fungus excreted cutinase during the penetration of the host pisum sativum. This result constitutes the most specific and strongest evidence for an enzymic penetration of a plant cuticle by a pathogen during infection.Cuticle constitutes the first barrier between a higher plant and its environment. The mode of penetration of this bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 5 publications
0
35
0
Order By: Relevance
“…The sequence around the catalytic domain is highly conserved and provides a signature pattern for cutinases (Kolattukudy et al, 1985). A critical role for fungal cutinases in the penetration of unwounded host tissues was demonstrated for some fungi by the use of antibodies, inhibitors and by using cutinase deficient fungal mutants (Dickman and Patil, 1986;Dickman et al, 1983;Maiti and Kolattukudy, 1979;Shaykh et al, 1977). In addition, recent gene disruption studies on the cutinase gene of Pyrenopeziza brassicae, an ascomycete, showed molecular evidence that cutinase activity is required for pathogenicity (Li et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The sequence around the catalytic domain is highly conserved and provides a signature pattern for cutinases (Kolattukudy et al, 1985). A critical role for fungal cutinases in the penetration of unwounded host tissues was demonstrated for some fungi by the use of antibodies, inhibitors and by using cutinase deficient fungal mutants (Dickman and Patil, 1986;Dickman et al, 1983;Maiti and Kolattukudy, 1979;Shaykh et al, 1977). In addition, recent gene disruption studies on the cutinase gene of Pyrenopeziza brassicae, an ascomycete, showed molecular evidence that cutinase activity is required for pathogenicity (Li et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Factors present in cuticle or cell wall, such as dihydroxy C^g-fatty acid, 18-hydroxy-9,10-epoxy Cj^-acid or 9,10,18-trihydroxy Cjg-acid, pectin, or cellulose, have been added to culture media in order to induce the formation of cutin-or cell wall-degrading enzymes in byphae (Forster & Rashed, 1985 ;Kolattukudy, 1985 ;Crawford & Kolattukudy, 1987;Koller & Parker, 1989;Urbanek, 1989;Perez Artes & Tena, 1990;Yazdi, Woodward & Radford, 1990;Riou, Freyssinet & P^evre, 1991). Altbough it is unclear whether or not hypbae formed in liquid culture resemble functional germ tubes, differences between cutinase formed in liquid culture and tbat formed on the host have not been detected with immunological techniques (Sbaykh, Soliday & Kolattukudy, 1977).…”
Section: Production Of Cuticle-and Cell Wall-degrading Enzymes By Hyphaementioning
confidence: 99%
“…The identified xenognosins were unlike any plant hormone known to mediate developmental commitments (Lynn et al, 1981), and surprisingly were not found to be present in host root exudates. Active compounds did appear after host wounding, leading to the proposal that the parasite released oxidative enzymes, similar to cutinase exudation by Fusarium solani during haustorial penetration (Shaykh et al, 1977), to liberate xenognosins from the host cell surface (Chang and Lynn, 1986). This hypothesis was tested directly by screening for enzymatic activity.…”
Section: What Signals Host Commitment?mentioning
confidence: 99%